2019
DOI: 10.1111/1755-6724.13861
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Shale Reservoir and Sweet Spot Identification of the Lower Cambrian Niutitang Formation in Northwestern Hunan Province, China

Abstract: The accumulation and productivity of shale gas are mainly controlled by the characteristics of shale reservoirs; study of these characteristics forms the basis for the shale gas exploitation of the Lower Cambrian Niutitang Formation (Fm), Southern China. In this study, core observation and lithology study were conducted along with X‐ray diffraction (XRD) and electronic scanning microscopy (SEM) examinations and liquid nitrogen (N2) adsorption/desorption and CH4 isothermal adsorption experiments for several exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Once the R o exceeds 3%, the organic pores in the shale nearly disappear (Wang et al 2016a, b, c;Gu et al 2018;Wang et al 2020a, b). The content of quartz is high in the Niutitang Formation shale (Qin et al 2019), and the quartz presents with five different types, silt-size/sand-size detrital quartz, siliceous skeletons, overgrowth nucleated around detrital quartz, matrix-dispersed microcrystalline quartz and aggregates of euhedral quartz, respectively, and the authigenic quartz is the dominant type (Dong et al 2021). However, Liu et al (2018) reported that the high content of quartz in the Niutitang Formation shale profits from the biogenetic quartz (Dong et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Once the R o exceeds 3%, the organic pores in the shale nearly disappear (Wang et al 2016a, b, c;Gu et al 2018;Wang et al 2020a, b). The content of quartz is high in the Niutitang Formation shale (Qin et al 2019), and the quartz presents with five different types, silt-size/sand-size detrital quartz, siliceous skeletons, overgrowth nucleated around detrital quartz, matrix-dispersed microcrystalline quartz and aggregates of euhedral quartz, respectively, and the authigenic quartz is the dominant type (Dong et al 2021). However, Liu et al (2018) reported that the high content of quartz in the Niutitang Formation shale profits from the biogenetic quartz (Dong et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…More and more researchers are paying attention to the development of these pores and their controlled factors, and have discovered many important results. Generally speaking, shale pore development is mainly affected by thermal maturity, organic matter abundance, kerogen maceral and mineral content, as well as other factors [10][11][12][13][14][15]. The relationship between thermal evolution degree and pore structure characteristics has obvious stage characteristics, which means that the porosity increases when the Ro(vitrinite reflectance) of the Niutitang shale reservoir is between 0.6% and 3%, and the pore structure is well developed; however, when Ro is more than 3.5%, it is adverse to pore development, and can even destroy the original pore structure and eventually lead to the disappearance of the pores [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between thermal evolution degree and pore structure characteristics has obvious stage characteristics, which means that the porosity increases when the Ro(vitrinite reflectance) of the Niutitang shale reservoir is between 0.6% and 3%, and the pore structure is well developed; however, when Ro is more than 3.5%, it is adverse to pore development, and can even destroy the original pore structure and eventually lead to the disappearance of the pores [10,16]. Some scholars have also proposed that organic pores and micro-cracks develop in large quantities in the high-mature to over-mature stage [11,12]. In the polar development stage of organic pores, there is a positive correlation between TOC and pore volume of different pore sizes and total pore volume [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Mesopores are commonly acknowledged to dominate the pore volume, and mineral matrix pores can also be observed in transitional shale, but organic matter (OM) pores are uncommon. 5−13 Moreover, the pore volume in marine shale is relatively equal to that in transitional shale according to the experimental analysis of gas adsorption, 6,14,15 which indicates the potential of transitional shale gas production and is worth further study.…”
Section: Introductionmentioning
confidence: 99%